Isolation and antimicrobial resistance profile for Enterococcus spp in goat milk processing plants (Research, Society and Development, 2022)
The antimicrobial resistance of Enterococcus spp in the dairy industry has been reported over the years, making it a potential source of contamination for the finished product as this microorganism is resistant to the pasteurization process. Thus, the present study aimed to evaluate the antimicrobial resistance profile of Enterococcus spp isolated from goat milk processing plants. Samples were collected and seeded on agar with 5% defibrinated goat blood. The isolates were confirmed by the MALDI TOF technique. The greatest resistance was observed for norfloxacin, followed by tetracycline and chloramphenicol and vancomycin. Nitrofurantoin and linezolid showed the highest sensitivity rates for the strains studied. This research demonstrates the need for sanitary policies for the quality control of goat's milk with the presence of pathogens resistant to pasteurization processes with antimicrobial resistance, making it a potential risk to the health of the population.